2020
DOI: 10.1371/journal.pone.0234601
|View full text |Cite
|
Sign up to set email alerts
|

Predicted DRD4 prefrontal gene expression moderates snack intake and stress perception in response to the environment in adolescents

Abstract: Body weight is substantially determined by eating behaviors, which are themselves driven by biological factors interacting with the environment. Previous studies in young children suggest that genetic influences on dopamine function may confer differential susceptibility to the environment in such a way that increases behavioral obesity risk in a lower socioeconomic status (SES) environment but decreases it in a higher SES environment. We aimed to test if this pattern of effect could also be observed in adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 107 publications
1
8
0
Order By: Relevance
“…Extending this work, we have used a novel genomic approach that imputes the gene expression of DRD4 in PFC using individual level genomic information 27 to find that genetically regulated expression of the DRD4 gene in PFC moderated effects of socioeconomic background on emotional eating in 48-month old children, and desire to drink in 60-month old children 22 . A similar differential susceptibility effect was found in the current adolescent cohort, such that lower predicted PFC DRD4 expression was associated with greater food intake in the satiated state, in the context of lower socioeconomic status 20 . This approach represents a significant addition to existing work by examining specific effects of genetically-driven mechanisms on the biological substrate of interest, in this case brain circuits including and interacting with prefrontal cortex.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Extending this work, we have used a novel genomic approach that imputes the gene expression of DRD4 in PFC using individual level genomic information 27 to find that genetically regulated expression of the DRD4 gene in PFC moderated effects of socioeconomic background on emotional eating in 48-month old children, and desire to drink in 60-month old children 22 . A similar differential susceptibility effect was found in the current adolescent cohort, such that lower predicted PFC DRD4 expression was associated with greater food intake in the satiated state, in the context of lower socioeconomic status 20 . This approach represents a significant addition to existing work by examining specific effects of genetically-driven mechanisms on the biological substrate of interest, in this case brain circuits including and interacting with prefrontal cortex.…”
Section: Introductionsupporting
confidence: 77%
“…We therefore investigated whether predicted PFC DRD4 expression would be associated with altered brain food cue responsiveness in adolescents. Given known sex differences in brain maturation during adolescence 30 as well as in eating behavior 20 , obesity 23 , and neural responses to food cues 31 , 32 , likely driven by social environment as well as biological factors 25 , we examined relationships in females and males separately. Since obesity is associated with eating in the presence of satiety 33 , and with reduced neural satiety responses 32 , we examined effects of DRD4 PFC expression on neural food cue responses in the satiated/fed, rather than the fasted, state.…”
Section: Introductionmentioning
confidence: 99%
“…Results should be considered significant only within a certain range of interest, that is ±2SD of the observed predictor variable. Values for the PoI index should be approximately within 0.40 and 0.60, and for 6 http://www.yourpersonality.net/interaction the PA index should be close to 0.50 (Roisman et al, 2012;Portella et al, 2020).…”
Section: Analysis Of Differential Susceptibilitymentioning
confidence: 99%
“…However, a rival explanation for some of these associations is diathesis-stress, in which poor developmental experiences (e.g., low-quality parenting) are most likely to impact the development of individuals who carry vulnerability factors that result in maladaptation. Ascertaining whether parenting interacts with genetic factors in either a differential susceptibility or diathesis-stress manner is a subject of ongoing exploration ( Garmezy et al, 1984 ; Roisman et al, 2012 ; Portella et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies have identified thousands of loci associated with complex traits [15]. The use of PrediXcan is increasingly common in genetic association studies [16][17][18][19][20][21][22][23][24] and recently contributed to the identification of genes associated with lipid levels and schizophrenia [19,20], cutaneous squamous cell carcinoma [23], lung cancer [24], and colorectal cancer [21]. For example, TRIM4 and PYGL, both related to cellular metabolic programming, were associated with CRC risk [21].…”
Section: Introductionmentioning
confidence: 99%